2019
DOI: 10.4239/wjd.v10.i2.63
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance is associated with subclinical vascular disease in humans

Abstract: Insulin resistance is associated with subclinical vascular disease that is not justified by conventional cardiovascular risk factors, such as smoking or hypercholesterolemia. Vascular injury associated to insulin resistance involves functional and structural damage to the arterial wall that includes impaired vasodilation in response to chemical mediators, reduced distensibility of the arterial wall (arterial stiffness), vascular calcification, and increased thickness of the arterial wall. Vascular dysfunction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 92 publications
2
24
0
2
Order By: Relevance
“…Moreover, IR accompanied by hyperglycaemia and hypertriglyceridaemia has been demonstrated to be correlated with elevated plasminogen activator inhibitor-1 levels, leading to decreased fibrinolytic activity and increased thrombotic events [28,29]. Furthermore, IR has been shown to be associated with structural and functional arterial wall injuries, such as endothelial dysfunction, impaired vasodilation, increased arterial stiffness, increased intima-media thickness, and increased coronary artery calcification, which are highly predictive of future CV events [30]. Notably, several studies confirmed [31].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IR accompanied by hyperglycaemia and hypertriglyceridaemia has been demonstrated to be correlated with elevated plasminogen activator inhibitor-1 levels, leading to decreased fibrinolytic activity and increased thrombotic events [28,29]. Furthermore, IR has been shown to be associated with structural and functional arterial wall injuries, such as endothelial dysfunction, impaired vasodilation, increased arterial stiffness, increased intima-media thickness, and increased coronary artery calcification, which are highly predictive of future CV events [30]. Notably, several studies confirmed [31].…”
Section: Discussionmentioning
confidence: 99%
“…An independent association was reported between insulin resistance (assessed by HOMA-IR) and cardiovascular events both in subjects with and without diabetes [ 8 10 ]. In addition, several studies provide compelling evidence of an association between insulin resistance and subclinical vascular injury involving functional and structural damage to the arterial wall that is not explained by traditional risk factors [ 11 ]. Early atherosclerosis detected by intima-media thickness is also independently associated with insulin resistance in patients with type 2 diabetes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ряд исследований показал, что наличие СД 2 типа у пациентов с АГ значительно усугубляет процессы сосудистого ремоделирования. При этом гипергликемия и инсулинорезистентность тканей являются основными триггерами патогенетических процессов, которые усугубляют артериальную жесткость и повышают восприимчивость сосудистой стенки к развитию атеросклероза [13].…”
Section: Vascular Remodeling Markers In Hypertension With Type 2 Diabunclassified